(untitled) (Maharaja Surajmal Institute Law Journal, 2026)
Fairness perceptions in the workplace have long been recognized as a cen tral determinant of employee motivation, performance, and organizational harmony. Organizational justice refers to employees’ subjective assessments of fairness concerning outcomes, procedures, and interpersonal treatment. This paper provides a historical and conceptual analysis of the evolution of organizational justice, tracing its development from early notions of rela tive deprivation (Stouffer et al., 1949) to contemporary, multidimensional frameworks. The review identifies three major intellectual phases—dis tributive, procedural, and interactional justice—and examines how each stream has cumulatively shaped the field. The paper highlights the interplay among these perspectives and underscores the integrative movement that positions justice as a multifaceted construct influencing employee attitudes and behaviors across organizational contexts.